EVALUATING THE CAREER ORIENTATION OF FINAL YEAR PHARMACY STUDENTS AT VINH MEDICAL UNIVERSITY IN 2023 - Dang Thi Van Anh, Nguyen Thi Minh Thuy (Tạp chí Khoa học, 2024)
Survey results on the career orientation of Pharmacy students in courses D1A and D2A show that the majority of students want to become consulting pharmacists at pharmacies and pharmaceutical sales representatives. The main deciding factor when choosing a job is income level, with most expecting an income after graduation of between 8 and 12 million VND. However, students also face great difficulties in applying for jobs due to lack of experience and limitations in foreign languages and information technology. The skills that students want to receive additional training in are mainly sales, communication and presentation skills. The results also show that most students have determined to develop a job search plan in the near graduation period, only a few do not have plans because they have been arranged by their families or attracted by local policies.